Normalization of the Use of the State Budget in the Nusantara Capital City Megaproject: Norman Fairclough’s Critical Discourse Analysis - Deni Indrawan; Andi Muhammad Aqshal (Journal of Primary Education Innovation and Research, 2026)
The relocation project of the Nusantara Capital City (IKN) is a national strategic issue whose meaning continues to be negotiated with the public through mass media. The media act not merely as a mirror of reality, but as a discursive arena capable of producing and reproducing ideology. This study aims to critically investigate the construction of language and ideology in the news text entitled “Phase II of IKN Accelerated, the State Budget Still Becomes the Backbone,” published by the Kompas.com news portal in mid-2025. Using a descriptive qualitative method, this study applies Norman Fairclough’s Critical Discourse Analysis (CDA) framework, which analyzes phenomena through three dimensions: microstructural (text), mesostructural (discursive practice), and macrostructural (sociocultural practice). The results of the textual analysis prove the use of metaphors such as “backbone” as well as passive grammatical structures that obscure the subject of policy makers in order to minimize potential resistance. In the dimension of discourse practice, a dominance of monological narratives was found, referring to the allocation of fantastic figures without presenting counter-discourse from civil society regarding the initial promise of IKN financing. Meanwhile, in the dimension of sociocultural practice, this news represents the hegemony of developmentalism ideology that legitimizes the intervention of State Revenue and Expenditure Budget (APBN) funds in order to maintain the sustainability of the megaproject during the political transition period. The conclusion of this study affirms that the journalistic language of online media functions as a state ideological apparatus that rationalizes and normalizes the shift in the financing scheme of the IKN project.